Patient-adjusted versus health professional-adjusted insulin dosing for type 2 diabetes mellitus - Ng, Chirk Jenn; Liew, Su May; Vethakkan, Shireene Ratna; Abdullah, Adina; Teng, Cheong Lieng (Cochrane Collaboration, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To evaluate the efficacy and safety of patient-adjusted versus health professional-adjusted insulin dosing in people with type 2 diabetes mellitus.